2007
DOI: 10.1007/s11192-007-1676-1
|View full text |Cite
|
Sign up to set email alerts
|

Explaining international collaboration in global environmental change research

Abstract: This paper maps the domain of earth and environmental sciences (EES) and investigates the relationship between cognitive problem structures and internationalisation patterns, drawing on the concepts of systemic versus cumulative global environmental change (GEC) and mutual task dependence in scientific fields. We find that scientific output concentration and internationalisation are significantly higher in the systemic GEC fields of Meteorology & Atmospheric Sciences and Oceanography than in the cumulative GEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 19 publications
2
30
0
2
Order By: Relevance
“…3.2.4), which is in line with the general trends observed in global environmental change research (e.g. Jappe, 2007).…”
Section: Trends In Geographiessupporting
confidence: 89%
“…3.2.4), which is in line with the general trends observed in global environmental change research (e.g. Jappe, 2007).…”
Section: Trends In Geographiessupporting
confidence: 89%
“…A similar shift is observed in other regions such as CAN (early GLOF works published at WOS by Vilímek et al (2005) compared to the recent work of Colonia et al (2017)) or HKH (Watanabe and Rothacher (1996) and the recent work of Prakash and Nagaraja (2017)). A trend in the internationalization of GLOF research teams has also been observed in the past few decades (see 3.2.4), which is in line with the general trends observed (e.g., Jappe, 2007). Manually assigned bilateral research ties (each tie represents one joint publication between two countries) A matrix of 468 bilateral research ties * institutions / institutions-enhanced ** the first GLOF research item published in the WOS database (Jackson, 1979) *** the highest number of references cited by one item (Girard et al, 2015) **** the highest number of citations obtained by one item by the end of 2016 (Hemming, 2004) Nat.…”
Section: Trends In Geographies 20supporting
confidence: 86%
“…The predominance of authors from this country has been reported in several studies (FAZEY et al, 2005;CARNEIRO et al, 2008;NABOUT et al, 2010). Part of the reason for this must be the greater investment in infrastructure and research (MUGNAINI et al, 2004;JAPPE, 2007). However, a high proportion of studies on Chl-a have been conducted in China.…”
Section: Discussionmentioning
confidence: 92%